SENIOR HIGH SCHOOL TEACHER PERFORMANCE : HOW TO ROLE LEADERSHIP, SELF EFFICACY AND ORGANIZATIONAL COMMITMENT? - Fabanyo, Heren (Journal of Industrial Engineering & Management Research, 2019)
The purpose of this study was to analyze the relationship of leadership to teacher performance, self-efficacy to teacher performance and organizational commitment to the performance of senior high school teachers in Pati. The type of this research is quantitative research. This study was conducted to determine the effect of leadership, self-efficacy and organizational commitment as independent variables on teacher performance as the dependent variable. In this study, the research population was 166 elementary school teachers in senior high school in Pati. The sampling method is Stratified Random Sampling. The analysis in this study uses Structural Equation Modeling and the data processing uses the SmartPLS software program. Data were collected by distributing online questionnaires to 166 teachers at senior high school in Pati. The results of this study are that there is a positive and significant relationship between leadership and teacher performance, there is a positive and significant relationship between self-efficacy and teacher performance, and there is a positive and significant relationship between organizational commitment and teacher performance.